Consequences of Residual Aluminium from Alum Coagulant on Humans - Jadhav M. V.; Mahajan Y. S. (International Journal of Research in Chemistry and Environment (IJRCE), 2011)
Coagulation flocculation is one of the important unit operation in water treatment it removes suspended solids and other impurities from water with the help of coagulants. The most commonly used coagulant in drinking water treatment plant is alum (aluminum sulphate). The presence of Aluminium in water for domestic supplies is due either to the addition of aluminum salts in the course of coagulation and flocculation treatment, or is caused by a low pH value of either surface or ground waters. Many researchers have done study on residual aluminium and its effects on humans. This review paper gives an overview of the presence of Aluminium in drinking water with reference to its speciation, removal, water supply and consequence on human health and the regulation of its levels in drinking water.